2008
DOI: 10.1097/yic.0b013e32830263de
|View full text |Cite
|
Sign up to set email alerts
|

A pooled analysis of two placebo-controlled trials of desvenlafaxine in major depressive disorder

Abstract: The efficacy, safety, and tolerability of desvenlafaxine (administered as desvenlafaxine succinate) were evaluated in two similarly designed, phase 3, randomized, double-blind, placebo-controlled, venlafaxine-extended-release-referenced, flexible-dose studies of outpatients with a primary diagnosis of major depressive disorder. Owing to a high placebo response, the individual studies were underpowered. Therefore, a post-hoc pooled analysis was performed (desvenlafaxine and placebo data were pooled; venlafaxine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 204 publications
(38 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Mean decreases in weight for DVS treatment groups were statistically signifi cant compared with baseline and placebo in both high and low dose trials. [31][32][33][34][35][36] In the DVS 400 mg group, there was a statistically signifi cant decrease in weight compared to the DVS 100 mg and 200 mg groups. Data pooled from 7 clinical trials, showed that treatment with DVS was associated with small mean decreases in weight in the short term (1 kg), which persisted up to 6 months with a small mean increase (Ͻ1 kg) and was comparable to placebo.…”
Section: Discontinuation Emergent Symptomsmentioning
confidence: 98%
See 4 more Smart Citations
“…Mean decreases in weight for DVS treatment groups were statistically signifi cant compared with baseline and placebo in both high and low dose trials. [31][32][33][34][35][36] In the DVS 400 mg group, there was a statistically signifi cant decrease in weight compared to the DVS 100 mg and 200 mg groups. Data pooled from 7 clinical trials, showed that treatment with DVS was associated with small mean decreases in weight in the short term (1 kg), which persisted up to 6 months with a small mean increase (Ͻ1 kg) and was comparable to placebo.…”
Section: Discontinuation Emergent Symptomsmentioning
confidence: 98%
“…The number of completers in the DVS group (72%) was lower than in either venlafaxine ER group (75-150 mg/day: 85%; 150-225 mg/day: 77%) or placebo (86%) in the pooled analysis. 36 Nausea was the most common reason cited for discontinuation among DVS patients in all studies, except for one study with DVS 200 mg (fl exible dose) 33 where insomnia (3%) was the most frequent reason for discontinuation.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
See 3 more Smart Citations